Thermophilic and alkaliphilic Actinobacteria: biology and potential applications - Shivlata, L; Tulasi, Satyanarayana (Frontiers in Microbiology, 2015)
Microbes belonging to the phylum Actinobacteria are prolific sources of antibiotics, clinically useful bioactive compounds and industrially important enzymes. The focus of the current review is on the diversity and potential applications of thermophilic and alkaliphilic actinobacteria, which are highly diverse in their taxonomy and morphology with a variety of adaptations for surviving and thriving in hostile environments. The specific metabolic pathways in these actinobacteria are activated for elaborating pharmaceutically, agriculturally, and biotechnologically relevant biomolecules/bioactive compounds, which find multifarious applications.